2008
DOI: 10.17221/10/2008-swr
|View full text |Cite
|
Sign up to set email alerts
|

Drought stress tolerance of two wheat genotypes

Abstract: Biotic and abiotic stress effects can limit the productivity of plants to great extent. In Hungary, drought is one of the most important constrains of biomass production, even at the present climatic conditions. The climate change scenarios, developed for the Carpathian basin for the nearest future predict further decrease in surface water resources. Consequently, it is essential to develop drought stress tolerant wheat genotypes to ensure sustainable and productive wheat production under changed climate condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…Wheat, barley and a triticale cultivar were evaluated in three season under three thermal condition: control and two timing of heating before anthesis and found stem elongation stage is most sensitive to high temperature stress (yield reduction 46%) Ugarte et al (2007) Hungary Wheat 'GK-Elet' and 'Mv-Emese' Pot culture experiment in growth chamber indicated that 'MvEmese'was good drought stress tolerance than GK-Elet Lukacs et al (2008) Bulgaria Two drought tolerant wheat ('Katya' 'Zlatitza') and two sensitive 'Sadovo' and 'Miziya')…”
Section: Introductionmentioning
confidence: 99%
“…Wheat, barley and a triticale cultivar were evaluated in three season under three thermal condition: control and two timing of heating before anthesis and found stem elongation stage is most sensitive to high temperature stress (yield reduction 46%) Ugarte et al (2007) Hungary Wheat 'GK-Elet' and 'Mv-Emese' Pot culture experiment in growth chamber indicated that 'MvEmese'was good drought stress tolerance than GK-Elet Lukacs et al (2008) Bulgaria Two drought tolerant wheat ('Katya' 'Zlatitza') and two sensitive 'Sadovo' and 'Miziya')…”
Section: Introductionmentioning
confidence: 99%
“…Potential evapotranspiration was determined by the pan evaporation method (Szász, 1997): a pan with a large surface was filled with water and placed next to the soil columns, and its weight loss was regularly monitored. The potential evapotranspiration rate was found to be constant and equal to 0.254 10 -3 m 3 day -1 (Lukács et al, 2008).…”
Section: Materials and Methods Laboratory Experimental Set Upmentioning
confidence: 90%
“…For mathematical modelling of the soil water balance elements under non-regular conditions we used data, obtained from the stress diagnosis set up introduced by Lukács et al (2008). The system consisted of eight soil columns with winter wheat, placed in identical plexiglass boxes with an area of 0.15x0.15 m 2 (Fig.…”
Section: Materials and Methods Laboratory Experimental Set Upmentioning
confidence: 99%
See 2 more Smart Citations